1996
DOI: 10.1007/bf02532401
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor antagonists prevent acute ammonia toxicity in mice

Abstract: We proposed that acute ammonia toxicity is mediated by activation of NMDA receptors. To confirm this hypothesis we have tested whether different NMDA receptor antagonists, acting on different sites of NMDA receptors, prevent death of mice induced by injection of 14 mmol/Kg of ammonium acetate, a dose that induces death of 95% of mice. MK-801, phencyclidine and ketamine, which block the ion channel of NMDA receptors, prevent death of at least 75% of mice. CPP, AP-5, CGS 19755, and CGP 40116, competitive antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 71 publications
3
71
0
2
Order By: Relevance
“…While considerable evidence documents that microglial activation contributes to the pathogenesis of AHE (as noted above), the reason for the absence of microglial activation in their study is not clear. However, these investigators used a relatively high concentration of ammonia ( pathophysiologically relevant as this concentration of ammonia induces acute deterioration of neurological function, development of myoclonic seizures and death within 5-10 min after ammonia injection, [65][66][67] thereby precluding the subsequent identification of microglial activation. The basis for such deterioration following treatment with high levels of ammonia is not known, but it suggests the possibility of some generalized negative systemic event(s) (e.g., in heart or lung) occurring as a consequence of the hyperammonemia.…”
Section: Inflammation In Hepatic Encephalopathymentioning
confidence: 99%
“…While considerable evidence documents that microglial activation contributes to the pathogenesis of AHE (as noted above), the reason for the absence of microglial activation in their study is not clear. However, these investigators used a relatively high concentration of ammonia ( pathophysiologically relevant as this concentration of ammonia induces acute deterioration of neurological function, development of myoclonic seizures and death within 5-10 min after ammonia injection, [65][66][67] thereby precluding the subsequent identification of microglial activation. The basis for such deterioration following treatment with high levels of ammonia is not known, but it suggests the possibility of some generalized negative systemic event(s) (e.g., in heart or lung) occurring as a consequence of the hyperammonemia.…”
Section: Inflammation In Hepatic Encephalopathymentioning
confidence: 99%
“…Part of the cGMP formed is released into the extracellular space where it can be collected and served as a marker of NMDA-receptor-mediated NOS activity. This pathway is blocked by the pre-treatment of MK-801, a glutamate (NMDA) receptor antagonist (Hermenegildo et al, 1996(Hermenegildo et al, , 2000. Overactivation of NMDA receptors leading to an increase in NMDA/NOS/cGMP pathway has been shown to occur in acute hyperammonemia (Marcaida et al, 1992;Montoliu et al, 2002).…”
Section: Limited Concentrations Of Glutamine Synthetase Enzyme Substratementioning
confidence: 99%
“…During aestivation, ammonia excretion would be impeded, leading to its accumulation in the body. Since ammonia is toxic (Cooper and Plum 1987;Hermenegildo et al 1996;Ip et al 2001;Brusilow 2002;Felipo and Butterworth 2002;Rose 2002), African lungWshes have to avoid ammonia toxicity during aestivation, and they achieve this through an increase in urea synthesis (Smith 1930(Smith , 1935Janssens 1964;Janssens and Cohen 1968a, b) and a suppression of N production as ammonia (see Ip et al 2004;Chew et al 2006 for reviews). Recently, Chew et al (2004) demonstrated that the rate of urea synthesis increased 2.4-to 3.8-fold and the rate of N production decreased by 72% in P. dolloi during 40 days of aestivation in air (normoxia) when compared with the immersed control.…”
mentioning
confidence: 99%